AL-QUR'AN INSIGHTS ABOUT DEVELOPMENT - Munawarah, Zakiah Al; Haddade, Hasyim (Ma'had Aly As'adiyah Sengkang, 2024)
The purpose of this article is to examine the verses of the Qur'an which discuss Intentional actions. Normative theological research is the type of research used. Looking for book references in the form of tafsir, fiqh, journals and other references related to the subject of study is how the data collection process is carried out. Research findings show that the Qur'an only uses three vocabulary terms to describe deliberation: shura, shawir, and tasyawur. These terms basically refer to a group of people having a discussion, where each person expresses their opinion, and the best opinion is then decided by deliberation as follows: taking honey from a bee colony to create delicious honey in an effort to create social life. One that is serene, and filled with a sense of unity and harmony. The Qur'an emphasizes the value of community involvement in solving real world problems. Each community is allowed to decide on its own specific patterns and techniques because circumstances at any given time may force a community to differ.